Financial sustainability and business income generating in the non-profit sector - Rochat, Ludovic (Department of Social Development, 2016)
This study aimed to assess the perceptions of funding practices and level of financial sustainability amongst non-profit organisations in selected parts of the world. Furthermore, the study looked at the degree to which NPOs employ trading activity to help fund and improve financial sustainability. Utilising a quantitative method, the study used an online survey tool to gather financial information from 72 NPOs in six different countries - Australia, Canada, India, Nigeria, South Africa and the UK. This sample was derived from an international database called Idealist.org. Data was analysed using a Microsoft Excel spreadsheet and presented thematically to reflect the major findings of the research. It was found that NPOs around the world are crucially in need of extra income and may not survive if new income-generating alternatives are not found. This is largely due to NPOs being overly reliant on a donor-dependency model to raise funds, which is creating more and more financial insecurity. This model has limited financial sustainability, as the competition for funding has dramatically increased in recent years. All of these facts have made NPOs realise that it is necessary to diversify their income sources and become more financially self-reliant. This study explored one self-financing method, trading activity, which has the potential to help NPOs to become more financially stable. The research found that most NPOs do not perceive trading as negatively as it was once perceived and would consider using it if more support were given to them. In order to move in this direction, this study has formulated some recommendations that NPOs can use to start their own commercial activity, attain a more prosperous financial situation and fund their social mission.